Faktor Faktor Pengambilan Keputusan Pembelian Masyarakat Terhadap Produk Daging Sapi Segar Dan Produk Olahan Di Kota Wisata Batu - Karunia Setyowati Suroto; Ariani Trisna Murti; Farida Kusuma Astuti (Universitas Islam Kadiri, 2021)
Batu Tourism City is a city with many tourist destinations where there are many places to eat around tourist attractions and hotels that require businesses and households to meet the needs of food ingredients, one of which is beef, both fresh and processed. The research was conducted in Pasar Besar, Pasar Gentengan, and Pasar Pesanggrahan in Kota Wisata Batu on April 8, 2021 – August 8, 2021. The aim of this study was to determine the factors that influence public purchasing decisions for fresh and processed beef simultaneously and partially. The sampling of the research was carried out using the accidental sampling method with a total of 100 respondents. The samples used are consumers who buy fresh and processed meat in the three markets. Primary data processing analysis uses multiple linear regression approach with SPSS 22 measuring instrument. The results of calculating primary processing that all independent variables, product, price, place, promotion, and service provide a positive relationship and correlation of 0.724 or 72% on consumer purchasing decisions. in buying fresh and processed beef products at the study site, while the remaining 28% was influenced by independent variables outside the study. The conclusion that can be drawn from the results of the study is that the independent variables that have a dominant influence are the price and place variables which have an influence of 0.299 and 0.274 respectively. The promotion variable produces a value of 0.089 so it has no significant effect on consumer purchasing decisions. Suggestions from the research are that the market should promote directly through print media so that consumers can find out and automatically increase consumer interest in buying fresh and processed meat in Batu Tourism City.